Macroeconomic aspects of comprehensive costs of assets as a prerequisite for equipping the defense system with weapons and military equipment - Savić, Aleksandar O.; Mihajlović, Milan M.; Božović, Ivan D. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The activity of managing the budget funds of the Ministry of Defense and the Serbian Armed Forces (MoD and AF) does not accept even minimal mistakes in the procurement of weapons and military equipment (WME). Equipping the Serbian Armed Forces with weapons and military equipment must be economically justified because a large part of the budget is allocated for that purpose. The goal of the research is to look at the economic aspect of treating costs as a prerequisite for the process of equipping the defense system with weapons and military equipment. Methods: For the purposes of the research, we used analytical and descriptive methods in order to see the comprehensive costs of assets that precede the effective equipping of the Ministry of Defense and the Armed Forces with WME. The research included the analysis of 18 review and research papers, which we analyzed in accordance with the Rulebook on equipping the Serbian Armed Forces with weapons and military equipment. Results: The results of the research indicate that economic justification is expressed implicitly by the ratio of intangible benefits and achieved goals to the invested funds. The most common reason why economic justification is not expressed explicitly by the difference between the initial investment and the final asset quantity is the existence of a number of circumstances for making wrong investment decisions. Also, if the costs are not considered in detail during the entire life cycle of the investment, it can be assumed that the planned target result is not certain. Conclusion: The research indicates that not considering costs during the entire life cycle of the investment is the main reason for unplanned investments in the later stages and the emergence of numerous problems in the functioning of the defense system.